Stability analysis of TJ-II stellarator NBI driven Alfvén eigenmodes in ECRH and ECCD experiments. (6th May 2021) - Cappa, Á.; Varela, J.; López Bruna, D.; Ascasíbar, E.; Liniers, M.; Eliseev, L.G.; Fontdecaba, J.M.; García-Regaña, J.M.; González-Jerez, A.; Kharchev, N.K.; Medina, F.; Melnikov, A.V.; et al.
Abstract: In this paper, we analyze the impact of electron cyclotron resonance heating and electron cyclotron current drive on the Alfvénic instabilities driven by neutral beam injection observed in the TJ-II stellarator. An MHD stability analysis of driven Alfvén eigenmodes compatible with the experimental plasma parameters is carried out in order to compare with the data provided by magnetic coils, radiation monitors, and heavy ion beam probes. To this end, the vacuum magnetic configuration modified by the different levels of plasma current, the thermal plasma parameters and the fast ion pressure profiles generated by the co-injected neutral beam, are entered in the FAR3d gyro-fluid code in order to follow the linear evolution of the destabilized plasma equilibrium. Linear growth rates and radial location of the dominant predicted modes coincident in frequency with the observed fluctuations are presented. Despite the uncertainties related to the estimation of the rotational transform profile, the code predictions agree within reasonable accuracy with the experimental results.